Strengthening School Financial Management Capacity through Participatory Training for Administrative Staff in Underfunded Secondary Schools - Hanafiah Hanafiah; Syahril Hasan; Dodi Sukmayadi; Hajar Mukaromah; Yeny Rokhilawati (PT Inovasi Pratama Internasional, 2026)
Underfunded secondary schools in Indonesia rely heavily on limited BOS (School Operational Assistance) funds, yet administrative staff often lack adequate financial management capacity, threatening transparency and accountability. Participatory training offers a promising, cost-efficient capacity-building approach. This study examines the effect of a participatory training program on financial management knowledge, self-efficacy, and report accuracy among administrative staff in underfunded secondary schools, while also exploring participants’ subjective experiences. Methods: A mixed-method explanatory sequential design was employed, beginning with a one-group pretest-posttest quantitative phase (n=40 administrative staff from ten underfunded secondary schools) followed by qualitative semi-structured interviews with 15 purposively selected participants. The three-day participatory training incorporated simulations, case studies, role-play, and group discussions. Instruments included a knowledge test (α=0.85), a financial self-efficacy scale (α=0.89), and a financial report accuracy checklist (inter-rater κ=0.82). Data were analyzed using paired t-tests, Cohen’s d, and thematic analysis. Significant improvements were found in knowledge (t=12.34, p<0.001, d=2.01), self-efficacy (t=11.22, p<0.001, d=1.89), and report accuracy (t=9.87, p<0.001, d=1.64). Qualitative findings revealed three major themes: enhanced conceptual understanding, increased confidence and motivation, and improved collaborative practices. Participatory training effectively strengthens financial management capacity in resource-constrained school settings, enhancing both technical competence and professional agency. Integration of participatory approaches into continuous professional development policies is strongly recommended.